Mineralogical study of Kemaman coastal sediments off Terengganu, Malaysia - Abdullah, Nor Antonina; Mohamad Shazili, Noor Azhar; Abdurahman, Siti Waznah (Universiti Malaysia Terengganu, 2009)
The study was conducted to determine the mineral contents and the textural classes of the Kemaman coastal sediments. The samples were collected using Smith Mc Intyre grab on board KL PAUS ship owned by the Fishery Department, Malaysia. The sediments were collected from 12 stations and were analysed for mineral contents and textural classes of sediments. The result of X-ray Diffraction (XRD) analysis showed that quartz component was the dominant mineral in most of the stations, while other minerals, such as feldspar, illite, kaolinite, montmorillonite, chlorite and vermiculite, were found to be in trace amounts. For the textural class, two textural classes of the sediments were identified as sand and sandy loam. Sand texture was mostly found in the nearshore area while sandy loam was found in the offshore area.